THE IMPORTANCE OF ACADEMIC WRITING SKILLS COURSE AMONG UNIVERSITY STUDENTS - Bakhsh, Dr. Khuda; Shah, Sayyed Raheem Abbas; Shah, Sayyed Liaquat Hussain (IJRDO- Journal of Educational Research, 2018)
The study was designed to examine the perceived importance of academic writing skills course among university students. Five hundred linguistics teachers of GC University Faisalabad participated in this study. The researcher developed a questionnaire to measure the level of perceived importance of the course. The collected data was analyzed using descriptive statistics and regressions. . It was revealed that the academic writing skills (Vocabulary, unity, coherence, paraphrasing and polishing) course was perceived by the majority of the respondents as an important course for the acquisition of writing skills to tailor a good essay. The joint contribution of all of the five selected writing skills towards was sixty five percent to the variance in writing a good essay.  It was recommended that university should improve the delivery of the course by ensuring that both human and material resources are adequately provided for the realization of the anticipated results.